Using Evolutionary Algorithms and Ab Initio Calculations to Study the Crystal Structure of Intercalated Fe1/3TiS2 Compound - Chubarova, A. A.; Mamonova, M. V. (Bulletin of the Russian Academy of Sciences. Physics, 2024)
Ab initio calculations of the crystal structure and magnetic properties of intercalated Fe 0.33 TiS 2 compound are made using evolutionary machine learning algorithms. Spin‒orbit interaction is considered, and the band structure and density of states are calculated.